2011
DOI: 10.1007/s00586-011-1718-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch-induced apoptosis in rat annulus fibrosus cells is mediated in part by endoplasmic reticulum stress through nitric oxide production

Abstract: Various mechanical stresses in vivo induce disc cell apoptosis and intervertebral disc (IVD) degeneration, but the underlying molecular mechanism is not fully known. The aim of this study was to investigate the role of endoplasmic reticulum stress in cyclic stretch-induced apoptosis of rat annulus fibrosus (AF) cells. Flexercell Tension Plus system was used to apply cyclic stretch to rat annulus fibrosus cells at a frequency of 0.5 Hz with 20% elongation for 12, 24, 36, or 48 h. Apoptosis was detected by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 39 publications
(43 reference statements)
5
58
0
Order By: Relevance
“…The system induced the transcription of messenger ribonucleic acids of several growth factors, including BMP-2, BMP-4, prostaglandin I 2 synthase, and osteoblast-specific transcription factor in the cells from OPLL patients [9,19,24,30]. At the same time, several studies have suggested that ER stress response can be activated by mechanical stress in some cellular pathological processes, such as apoptosis in rat annulus fibrosus cells or human connective tissue cells [32]. Thus, based on above biological information, we hypothesized that PERK-mediated ER stress might be downstream mechanism in development of OPLL induced by some primary genetic or mechanical factors.…”
Section: Discussionmentioning
confidence: 99%
“…The system induced the transcription of messenger ribonucleic acids of several growth factors, including BMP-2, BMP-4, prostaglandin I 2 synthase, and osteoblast-specific transcription factor in the cells from OPLL patients [9,19,24,30]. At the same time, several studies have suggested that ER stress response can be activated by mechanical stress in some cellular pathological processes, such as apoptosis in rat annulus fibrosus cells or human connective tissue cells [32]. Thus, based on above biological information, we hypothesized that PERK-mediated ER stress might be downstream mechanism in development of OPLL induced by some primary genetic or mechanical factors.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress comprises stimuli that regulate a wide range of cellular responses including apoptosis, proliferation, inflammation, and differentiation in mammalian cells [35]. Many studies have shown that activation of the ER stress-induced apoptosis pathway contributes to various degenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and osteoarthritis [12, 13, 36]. 2-DG is well known to induce ER stress by inhibiting glycolysis and N-glycosylation of proteins [35, 37].…”
Section: Discussionmentioning
confidence: 99%
“…21 Recently, mechanical forces have been shown to induce apoptosis in several cell types. [22][23][24][25] Apoptosis is a cellular suicidal program crucial to the development and maintenance of multicellular organisms. 8 To our knowledge, the investigation described in the current study is the first to report the apoptosis in LF cells after mechanical stretch in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with previous reports. [22][23][24][25] Cyclic stretch can induce ROS generation and ROS are well-known to enhance apoptosis. 10,11 In this study, we found that cyclic stretch enhanced ROS production in LF cells in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%